Editor's Foreword. (18th December 2018) - Robertson, David
Abstract : This issue of Implicit Religion is a collection of papers first presented at the conference Contemporary Religion in Historical Perspective: Publics and Performances, held at the Open University at Kent's Hill, Milton Keynes, February 19–21, 2018. The conference was organized by Paul-François Tremlett, John Maiden, and myself. The call for papers solicited presentations on the themes of education, media, pilgrimage, politics, and ritual.